Portfolio choice and the effects of liquidity - Ana González; Gonzalo Rubio (SERIEs - Journal of the Spanish Economic Association, 2011)
This paper discusses how to introduce liquidity into the well known mean-variance framework of portfolio selection using a representative sample of Spanish equity portfolios. Either by estimating mean-variance liquidity constrained frontiers or directly estimating optimal portfolios for alternative levels of risk aversion and preference for liquidity, we obtain strong effects of liquidity on optimal portfolio selection. In particular, portfolio performance, measured by the Sharpe ratio relative to the tangency portfolio, varies significantly with liquidity.When the investor shows no preference for liquidity, the performance of optimal portfolios is relatively more favorable. However, it is also the case that, under no preference for liquidity, these portfolios display lower levels of liquidity. Finally, we also study how the aggregate level of illiquidity affects optimal portfolio selection.
Keywords: G10; G11; 330; liquidity; mean-variance frontiers; performance; portfolio selection; Portfolio-Management; Marktliquidität; Spanien